P-007 Granulomatous Lymphangitis of the Genitals: A Rare Variant of Cutaneous Crohn's Disease. (March 2016) - Foreman, Beth; Foulke, Galen; Tinsley, Andrew; Williams, Emmanuelle
Abstract : Background: Cutaneous Crohn's disease (CD) is a rare extraintestinal manifestation of CD distinguished by cutaneous non-caseating granulomatous lesions. It is commonly referred to as "metastatic CD" as the lesions are anatomically separate from the gastrointestinal tract, unlike fissures and fistulae, which arise through direct extension from involved bowel. Clinically it has a polymorphic presentation, from papules, nodules, and plaques, to ulcerations and edema, with predilection for lower extremities, trunk, and intertriginous areas. Granulomatous lymphangitis is an inflammatory non-pitting edema that may affect the mouth or genitals; in the appropriate clinical context it is considered to be a rare variant of cutaneous CD. Unlike classic cutaneous CD, which demonstrates dermal sarcoidal granulomas, granulomatous lymphangitis is characterized by the presence of intralymphatic histiocytes and edema. There are very few reported cases of cutaneous CD with isolated genital involvement in adults. Patients may present with any variant of cutaneous CD during periods of quiescent gastrointestinal disease, making diagnosis difficult. Methods: NA Results: We report a case of a 64-year-old Caucasian man presenting with 3-month history of scrotal and penile swelling and erythema. He was diagnosed with Crohn's colitis in 1973 and underwent partial colectomy and ileostomy. His Crohn's disease has remained well controlled without medications or flares over the past 30 years. Three months prior to presentation he developed progressive scrotal and penile swelling and erythema. He reported no systemic symptoms of fevers, chills, diarrhea, or bloody stool. Physical exam revealed marked non-pitting edema of the scrotum and penis with surrounding erythema. No ulceration or lymphadenopathy was present. Pelvic CT and scrotal ultrasound showed extensive edema with no localized fluid collection, concerning for cellulitis. Broad-spectrum antibiotics were started; however, due to lack of clinical improvement, a punch biopsy of scrotal skin was performed. Histopathologic examination revealed superficial and deep perivascular lymphocytes, plasma cells, and intralymphatic histiocytes, consistent with granulomatous lymphangitis. The patient was started on oral metronidazole with significant reduction in genital edema and erythema. Conclusions: Cutaneous CD is the least common dermatologic manifestation of Crohn's disease, and granulomatous lymphangitis is thought to be a unique presentation of cutaneous CD. The genitalia are the most common area of involvement in children; however, it is uncommonly reported in the literature for adult patients to present with activity isolated to the genitals. Our case is unique in that our patient had no active gastrointestinal disease and presented with isolated scrotal and penile swelling with erythema. This highlights the difficulty in diagnosing this rare entity; a high index of suspicion is essential to correctly diagnosing cutaneous CD and its variants. Due to various manifestations and lack of specific clinical features, patients with a history of CD presenting with unusual skin findings warrant a biopsy.